2011
DOI: 10.1017/s1751731110002302
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of hepatic amino acid uptake and net utilisation contributes to nitrogen economy or waste in lambs fed nitrogen- or energy-deficient diets

Abstract: We investigated the effect of relative changes in dietary nitrogen (N) and energy supply and the subsequent variations in net portal appearance (NPA) of nitrogenous and energy nutrients on the net amino acid (AA) uptake by the liver and net N supply to the peripheral tissues. Six lambs were catheterised across the splanchnic tissues and received, in a replicated Latin square, one of three dietary treatments. The diets were formulated to either match the requirements of N and energy (C), or supply only 0.8 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…In turn, the nutrients metabolized by liver originate not only from PDV but also from peripheral tissues (i.e. fatty acids from adipose and amino acids from muscle tissue), at increasing rates when the level of ME intake is below maintenance (Emery et al., ; Kraft et al., ). Moreover, the rates of increase in blood flow and oxygen consumption by PDV and total ST with increasing OM intake obtained in the present study were higher than those reported by Vernet et al.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the nutrients metabolized by liver originate not only from PDV but also from peripheral tissues (i.e. fatty acids from adipose and amino acids from muscle tissue), at increasing rates when the level of ME intake is below maintenance (Emery et al., ; Kraft et al., ). Moreover, the rates of increase in blood flow and oxygen consumption by PDV and total ST with increasing OM intake obtained in the present study were higher than those reported by Vernet et al.…”
Section: Discussionmentioning
confidence: 99%
“…Majdoub et al, 2003). Whether it is the high level of precursor supply or the imbalanced nutrient supply (as in Kraft et al, 2011 with N deficient diets) which is responsible for this plateau would remain to be confirmed. This reduced efficiency of hepatic conversion of precursors into glucose suggests a supply of precursors in excess of glucose demand.…”
Section: Hepatic Conversion Of Precursors Into Glucosementioning
confidence: 97%
“…Our results also showed that the average level of α-amino-N hepatic uptake (LSMeans) can be modified by the dietary N concentration, availability in propionate and hepatic glucose release. Direct experimental evidence was reported by Kraft et al (2011) who showed that a N deficient diet significantly limited the net hepatic uptake of α-amino-N, as a sparing mechanism, without modifying net glucose release (Loncke et al, 2009a).…”
Section: Domain Of Application Of the Modelsmentioning
confidence: 99%
“…As an example, in a ruminant study carried out by our group, a variation of N supply from 31 % to 20 % of energy intake did not affect total export or synthesis of albumin. In this case, hepatic uptake of EAA decreased at low N intakes but albumin synthesis did not, suggesting that export protein synthesis was already at its maximum, and that export protein synthesis was prioritised relative to hepatic catabolism via oxidative pathways ( 30 , 46 ) .…”
Section: Hepatic Protein Synthesismentioning
confidence: 87%
“…As for TAA, the hepatic uptake of four EAA (His, Met, Thr, Trp) is highly responsive to EAA influx to the liver ( 2 , 45 ) , whereas BCAA and Lys hepatic extraction rates are very small whatever their influx ( 25 , 46 ) . Only NEAA involved in inter-organ N and C cycling (Asn, Asp, Ala, Gln and Glu) present a hepatic uptake less responsive to influx ( 2 , 45 ) .…”
Section: Net Hepatic Uptake Of Amino Acids By the Livermentioning
confidence: 99%